FINANCIAL ANALYSIS OF RETAIL COMPANIES USING THE ALTMAN, SPRINGATE, ZMIJEWSKI, FULMER, AND GROVER BANKRUPTCY PREDICTION MODELS - Trisa Wahyuningsih; Lintang Venusita (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2022)
Bankruptcy analysis is a method to determine the company's financial condition using a bankruptcy prediction model. The purpose of this study is to determine the financial condition of retail companies in Indonesia listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period, which is measured using the Altman Z-Score, Springate, Zmijewski, Fulmer, and Grover bankruptcy prediction models. The type of research used is quantitative with a descriptive approach. The sample used is 28 retail companies published by the Indonesia Stock Exchange (IDX) for the 2019-2020 period. The data collection technique used is the documentation technique, in the form of annual financial reports of retail companies which are downloaded through www.idx.co.id. The results of data analysis showed that the bankruptcy prediction model of Altman, Springate, Zmijewski, Fulmer, and Grover gave different results, due to differences in the ratio variables used. Several retail companies are predicted to go bankrupt, due to the poor financial performance of the company, causing losses. However, most retail companies are still able to maintain a balance in financial performance and can minimize the risk of bankruptcy during the COVID-19 pandemic. For the company to avoid bankruptcy, the company must manage its financial performance as well as possible, such as regulating the level of sales, company liabilities, company assets, profit before taxes and interest, net income, retained earnings, receivables turnover, working capital, as well as minimizing operating costs company.